Effect of aging on lignin content, composition and enzymatic saccharification in Corymbia hybrids and parental taxa between years 9 and 12. (October 2016) - Healey, Adam L.; Lupoi, Jason S.; Lee, David J.; Sykes, Robert W.; Guenther, Joel M.; Tran, Kim; Decker, Stephen R.; Singh, Seema; Simmons, Blake A.; Henry, Robert J.
Abstract: Corymbia (a eucalypt) is an important forestry genus and a potential lignocellulosic bioenergy feedstock. The composition of the lignocellulosic cell wall significantly impacts pretreatment efficiency and conversion to biofuel but is variable and changes with age. In this study, we estimated Klason lignin content, composition, and monosaccharide (glucose and xylose) release after enzymatic saccharification of untreated and hydrothermally pretreated biomass from Corymbia parental species Corymbia torelliana (CT), Corymbia citriodora subsp. variegata (spotted gum; CCV), and interspecific F1 hybrids (CT × CCV) at ages 9 and 12 years from planting. Analysis of lignin composition derived from syringyl/guaiacyl monolignols (S/G) found significant differences among taxa, with CT S/G ratios (2.2 and 2.0) being significantly lower than CCV (2.6 and 2.3) or hybrids (2.5 and 2.3) at ages 9 and 12 respectively. In general, enzymatic saccharification yields from untreated biomass were significantly different among taxa, with CT (113 and 75 mg g −1 ) and hybrids (108 and 81 mg g −1 ) yielding significantly higher glucose from untreated biomass than CCV (82 and 56 mg g −1 ) at ages 9 and 12 respectively. Comparison of traits within taxa between ages 9 and 12 found S/G ratios and glucose yields from untreated biomass were significantly lower in CT, CCV and hybrid taxa. In conclusion, the formation of lignocellulosic cell walls is complex, influenced by genetics and age of material, requiring optimization of rotation age for biofuel production and other industrial processes. Highlights: Corymbia populations were evaluated for lignin content, composition and enzymatic saccharification at ages 9 and 12. S/G lignin composition and saccharification yields from untreated biomass were significantly different among taxa. S/G lignin composition and saccharification yield from untreated biomass was negatively impacted by age within each taxa.